Gender Roles and Gender Stereotypes in the Textbooks (Training and Practice : Journal of Educational Sciences, 2007)
In this study I analyse the representation of gender in the Hungarian textbooks, demonstrating the origins of the gender gap and how the differences is reproduced from generation to generation. In this paper I’m trying to attract attention on some stereotypes which are supposed to direct one’s way in life, even so they are often playing a big role in coming into existence of preconceptions and discrimination. My achievements show that - although some studies are pointing to the existence of the traditional gender roles and stereotypes in the textbooks – these papers have no influence on the current textbooks. These articles report the same: women are hidden on the pages of textbooks and in readings, only tr aditional acceptations appear in the division of labour. It can be declared that reality and the gender role in the textbooks are not correspondent.